Medical English As a Lingua Franca - Tweedie, M. Gregory (Developments in English as a lingua franca ;, 2022)
In this first book-length treatment of MELF, the authors assert that MELF represents an important contribution to our understanding of English as a Lingua Franca (ELF), in that existing ELF research has been limited to relatively low stakes communicative situations, such as interactions in business, academia, internet blogging or casual conversations. Medical contexts, in contrast, often represent situations calling for exceptional communicative precision and urgency. Providing both evidence from their own research and analysis from (the limited number of) existing studies, the authors offer a counterpoint to the optimism regarding communicative success prevalent in ELF. The book proposes a theoretical perspective on how the various features of healthcare communication serve as important variables in shaping interaction among speakers of ELF, further enlarging our understanding of this emerging sub-field.